ASSISTANCE IN THE PREPARATION OF EVIDENCE TO SUPPORT PERFORMANCE MANAGEMENT PRACTICES ON THE INDEPENDENT TEACHING (PMM) PLATFORM IN THE LEARNING COMMUNITY PALANGKA RAYA STATE 6 HIGH SCHOOL - Ni Putu Diah Agustin Permanasuri; Indah Gumilang Dwinanda; Mega Kurniawati; Cassiophea, Lola (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
The Assistance in the Preparation of Supporting Evidence for Performance Management Practices on the Merdeka Mengajar Platform (PMM) at SMA Negeri 6 Palangka Raya aims to support the government’s vision of enhancing the quality of human resources (HR) in the era of the Fourth and Fifth Industrial Revolutions. This program is designed to address the limitations faced by teachers in filling out supporting evidence for real actions, which are caused by a lack of technical training, limited understanding, and minimal access to information and digital literacy. The training program integrates Transformative Learning Theory, which emphasizes changing individuals' ways of thinking through learning experiences, and includes theory, hands-on practice, concrete examples, and question-andanswer sessions to enhance teachers' abilities to fill out supporting evidence in PMM. The results of the program indicate a significant improvement in competence, with 85% of participants passing, reflecting individual progress and an overall enhancement of the teaching process.